Engineering graphene properties by modulated plasma treatments. (April 2018) - Bianco, Giuseppe Valerio; Sacchetti, Alberto; Ingrosso, Chiara; Giangregorio, Maria Michela; Losurdo, Maria; Capezzuto, Pio; Bruno, Giovanni
Abstract: We demonstrate modulated H2 and O2 plasma treatments as an effective methodology for controlled chemical functionalization by hydrogen and oxygen atoms of single- and multi-layer chemical vapor deposition (CVD) graphene aiming at engineering material properties. The effects of the functionalization degree on the optical and transport properties of graphene are discussed with a twofold aim of (i) providing reproducible experimental protocols for tailoring graphene properties, and of (ii) providing insights into the chemical mechanisms involved in the plasma-processing of graphene with hydrogen and oxygen atoms. An unprecedented control over the graphene functionalization by hydrogen atoms is demonstrated together with the fine tuning of multi-layer graphene resistivity as well as the transition from metallic to semiconducting behavior with a gap opening. The interaction of oxygen atoms with multilayer graphene provides a strong modification of surface wettability without significant change in conductivity, thus suggesting that oxidation effects are mainly confined on the outmost graphene. Moreover, the air exposure of graphene oxidized by plasma treatment results in peculiar chemical mechanisms with important effect on the transport properties of the material. Finally, we investigate the restoration of graphene from graphene oxide by modulated hydrogen plasma. Graphical abstract: Image 1